Exploring sub-daily to seasonal variations in methane exchange in a single-crop rice paddy in central Japan. (April 2018) - Iwata, Hiroki; Mano, Masayoshi; Ono, Keisuke; Tokida, Takeshi; Kawazoe, Takahiro; Kosugi, Yoshiko; Sakabe, Ayaka; Takahashi, Kenshi; Miyata, Akira
Abstract: Season-long methane ( CH 4 ) exchange was observed in a rice paddy field in central Japan (Kanto Region) using the eddy covariance technique to clarify the variations in environmental controls on CH 4 exchange in different stages of cultivation. Before heading of rice plant, the CH 4 emission depended on wind speed and soil temperature. The soil temperature dependence can be due to an increase in CH 4 production, higher molecular diffusion, and higher conductance within rice plant at higher soil temperature. An occurrence of ebullitive emission was also suggested from the wind speed dependence. After heading was completed, relative humidity and water temperature influenced CH 4 emission. The amplitude of the diurnal variation in emission increased from 0.03 μ mol m − 2 s − 1 in the late pre-heading stage to 0.13 μ mol m − 2 s − 1 in the post-heading stage. Induced convective throughflow within the rice aerenchyma after the change in plant structure was attributable to this variation in environmental controls after the heading. After drainage, CH 4 emission was confined to short periods after strong rain events. The water level controlled the timing of emission, most likely by influencing the diffusion efficiency from the anoxic soil to the atmosphere and CH 4 oxidation in the surface oxic zone. The variation in the dominant transport pathway needs to be accounted for in terrestrial ecosystem models to accurately predict CH 4 emission from rice paddies. Highlights: Environmental controls on CH4 emissions varied among the cultivation stages of rice. Before the heading of rice, diffusion and ebullition were the dominant pathway. An occurrence of convective throughflow was suggested after rice plant heading.